Ink composition, printed matter, and laminate
By using resins with high glass transition temperature or soft point in the printing ink of the packaging material, combined with amino ester resin and other specific resins, the problem of degradation of oxygen barrier performance under high humidity conditions is solved, and excellent air barrier performance and heat resistance are achieved.
Patent Information
- Application Number
- JP2023155541
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
AI Technical Summary
The oxygen barrier performance of existing packaging materials has decreased under high humidity conditions, and the traditional air barrier film and glue layer has the problem that the materials are not resistant to moisture and heat, which affects the overall performance of the packaging.
Resin containing high glass transition temperature (Tg) or soft ing points, such as aminoester resin and/or aminoester urine resin, is used as the adhesive for printing inks, and aminoester resin and other specific resins are combined to improve the air barrier properties and heat resistance of the inks.
It achieves excellent air barrier performance under high humidity conditions, while improving the ink's cap resistance, adhesion and laminate strength, avoiding the material limitations caused by the use of air barrier film and glue.
Smart Images

Figure 2025047197000001 
Figure 2025047197000002 
Figure 2025047197000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an ink composition, a printed matter, and a laminate having gas barrier properties. [Background technology]
[0002] Packaging materials for food and industrial materials have been used in order to satisfy many required characteristics, including flexibility suitable for packaging. These materials are called flexible packaging materials and are made of various plastic films, vapor-deposited films with metals or metal oxides vapor-deposited, composite films made by multi-layer lamination of metal foils, etc. Required characteristics include resistance to contents, high performance against boiling and retort, durability to withstand harsh environments, gas and water vapor barrier properties to protect contents, low migration of material components into contents, low odor and taste, etc.
[0003] Among these, the most common method for satisfying the gas and water vapor barrier properties for protecting the contents is to use a film with gas barrier properties, such as an ethylene-vinyl alcohol copolymer or polyvinyl alcohol, but packaging materials made from these polymers have problems such as a significant decrease in oxygen barrier properties under high humidity conditions due to their hydrophilicity, as well as poor resistance to humidity and hot water.
[0004] In order to ensure a certain level of barrier properties even under these humidity conditions, a method is known in which an adhesive used in multilayer lamination of the plastic film, a vapor-deposited film with a metal or metal oxide vapor-deposited thereon, a metal foil, etc. is given a gas barrier function (see, for example, Patent Document 1).
[0005] On the other hand, printing ink is applied to the front or back of packaging materials, or to the inside of the laminate in the case of the aforementioned multi-layer laminated composite film materials, for the purpose of indicating the contents of the packaged goods, protecting the packaging materials, decoration, etc. In the case of packaging materials intended for gas barrier properties, as mentioned above, most of them use a film or adhesive having gas barrier properties, and provide a separate ink layer (see, for example, Patent Document 2).
[0006] Examples of printing inks that focus on the gas barrier properties of the ink itself include Patent Documents 3, 4, and 5. Patent Documents 3 and 4 improve the gas barrier properties by including a specific polyester resin or polyurethane resin. Patent Document 3 includes a vinyl chloride vinyl acetate copolymer. In response to the recent demand for improved recyclability of packages due to the mono-materialization of packages, polymers containing chlorine-based vinyl chloride monomers are known to have a negative effect on recyclability, and are therefore undesirable from the perspective of sustainability. Patent Document 4 also improves the gas barrier properties by including a specific polyester resin or polyurethane resin, but uses silica or silicone as an essential component to improve blocking resistance. However, these may have a negative effect on the appearance after lamination, especially when using a solvent-free adhesive, so it is desirable not to use these. Patent Document 5 also uses a resin containing vinylidene chloride monomer, which is undesirable from the perspective of package recycling, as with Patent Document 3. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2012-57033 A [Patent Document 2] Patent No. 5975189 [Patent Document 3] Patent No. 6372635 (DIC, Vinyl Chloride) [Patent Document 4] JP 2022-112187 A (DIC, Silica and Silicone) [Patent Document 5] JP 2018-24798 A (Dainichi Seika, Vinylidene Chloride) Summary of the Invention [Problem to be solved by the invention]
[0008] The problem to be solved by the present invention is to provide an ink composition which has gas barrier properties, and also has the performance required for an ink, such as blocking properties, adhesion, and lamination strength, while also having excellent recyclability and excellent appearance after lamination. [Means for solving the problem]
[0009] The inventors have solved the above problem by using a resin having gas barrier properties, such as an amorphous polyester resin and / or an amorphous polyester urethane resin, as a binder for the printing ink, and further using in combination a resin having a glass transition temperature (Tg) or softening point of 40°C or higher.
[0010] That is, the present invention provides a liquid printing ink characterized by containing: amorphous polyester resin (A) and / or amorphous polyester urethane resin (B) having an ester skeleton which is a polycondensate of a polycarboxylic acid component containing at least one of ortho-oriented aromatic dicarboxylic acids or anhydrides thereof and a polyhydric alcohol component containing at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol; and resin (C) having a glass transition temperature (Tg) or softening point of 40°C or higher.
[0011] The present invention also provides a printed matter and a laminate comprising a substrate and a printed layer printed and cured on the substrate, the printed layer being the ink composition described above. Effect of the Invention
[0012] The ink composition of the present invention can provide an ink composition having gas barrier properties while having the performance of an ink such as blocking properties, adhesion, and lamination strength. Therefore, it has an effect of imparting gas barrier properties to packaging materials without using a film or adhesive having gas barrier properties. It can be particularly suitably used for olefin-based mono-material packages having poor oxygen barrier properties. Furthermore, the present invention can provide a liquid printing ink that is excellent in recyclability and has excellent appearance after lamination because it does not contain any substance that inhibits recycling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (Definition of words) In the present invention, the liquid printing ink refers to a liquid ink applied to a printing method using a printing plate, such as gravure printing ink or flexographic printing ink, and is preferably gravure printing ink or flexographic printing ink. The liquid printing ink of the present invention does not contain an active energy curable component, i.e., it is an active energy ray non-reactive liquid printing ink. In the present invention, all "ink" refers to "printing ink." All "parts" refer to "parts by mass."
[0014] The present invention will now be described in more detail.
[0015] First, the amorphous polyester resin (A) and the amorphous polyurethane resin (B) used in the present invention will be described. These are preferably amorphous polyester resin (A) or amorphous polyester urethane resin (B) having an ester skeleton which is a polycondensation product of a polyvalent carboxylic acid component containing at least one of ortho-oriented aromatic dicarboxylic acid or its anhydride and a polyhydric alcohol component containing at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol. These amorphous polyester resins (A) and amorphous polyurethane resins (B) function as resins having gas barrier properties.
[0016] (Amorphous polyester resin (A)) The amorphous polyester resin (A) used in the present invention is obtained by polycondensation of a polycarboxylic acid component containing an ortho-oriented aromatic polycarboxylic acid component and a polyhydric alcohol component.
[0017] (ortho-oriented aromatic polycarboxylic acid component) Specifically, the ortho-oriented aromatic polycarboxylic acid component is orthophthalic acid and its anhydride. Orthophthalic acid and its anhydride have an asymmetric skeleton. It is therefore presumed that the rotation of the molecular chain of the resulting polyester is suppressed, which is why it is excellent in gas barrier properties. It is also presumed that due to this asymmetric structure, it exhibits non-crystallinity, provides sufficient adhesion to the substrate, and is excellent in adhesive strength and gas barrier properties. Furthermore, it has high solvent solubility, which is essential when used as a gravure ink, and is therefore characterized by excellent handleability.
[0018] (Aromatic polycarboxylic acids) The ortho-oriented aromatic polycarboxylic acid may be used in combination with other aromatic polycarboxylic acids, which is preferable. Specific examples of aromatic polycarboxylic acids include terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, and anhydrides or ester-forming derivatives of these dicarboxylic acids. These can be used alone or in a mixture of two or more. Among them, terephthalic acid and isophthalic acid are preferable.
[0019] Specific examples of other polycarboxylic acids that can be used in combination with the aromatic polycarboxylic acids include aliphatic polycarboxylic acids such as succinic acid, maleic acid, fumaric acid, adipic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid, and alicyclic polycarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid. These can be used alone or in a mixture of two or more. Acid anhydrides of these can also be used. Among these, it is preferable to use succinic acid, maleic acid, 1,3-cyclopentanedicarboxylic acid, and adipic acid in combination.
[0020] (Polyhydric alcohol component) Specific examples of the polyhydric alcohol used in the present invention include aliphatic diols such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, cyclohexanedimethanol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, dimethylbutanediol, butylethylpropanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol, and aromatic polyhydric phenols such as hydroquinone, resorcinol, catechol, naphthalene diol, biphenol, bisphenol A, bisphenol F, and tetramethylbiphenol, as well as ethylene oxide-extended products and hydrogenated alicyclic compounds thereof.
[0021] Among these, ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol are preferred, and ethylene glycol is more preferred, since it is presumed that the molecular chain is less likely to become excessively flexible as the number of carbon atoms between oxygen atoms decreases.
[0022] The polycondensation reaction between the polyvalent carboxylic acid component including the ortho-oriented aromatic polyvalent carboxylic acid component and the polyhydric alcohol component can be carried out by a known method.
[0023] (Amorphous polyester urethane resin (B)) The amorphous polyester urethane resin (B) used in the present invention is, for example, a reaction product of a polyester polyol resin having a hydroxyl group at the end among the amorphous polyester resins (A) and an isocyanate compound. Examples of the isocyanate compound include polyisocyanates having an aromatic structure in the molecular structure such as tolylene diisocyanate, diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, xylylene diisocyanate, etc., compounds in which a part of the NCO group of these polyisocyanates is modified with carbodiimide, alphanate compounds derived from these polyisocyanates, isophorone diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,3-(isocyanatomethyl)cyclohexane, etc. linear aliphatic polyisocyanates such as 1,6-hexamethylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and alphanate compounds thereof; isocyanurates of these polyisocyanates; allophanate bodies derived from these polyisocyanates; biuret bodies derived from these polyisocyanates; trimethylolpropane-modified adducts; and polyisocyanates which are reaction products of the above-mentioned various polyisocyanates with polyol components.
[0024] In addition, examples of the chain extender used in the amorphous polyester urethane resin include ethylenediamine, propylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, etc., as well as amine compounds having a hydroxyl group in the molecule such as 2-hydroxyethylethylenediamine, 2-hydroxyethylpropyldiamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, di-2-hydroxypropylethylenediamine, and di-2-hydroxypropylethylenediamine. These chain extenders can be used alone or in combination of two or more.
[0025] In addition, a monovalent active hydrogen compound can be used as a terminal blocking agent for the purpose of stopping the reaction. Examples of such compounds include dialkylamines such as di-n-butylamine, and alcohols such as ethanol and isopropyl alcohol. Furthermore, when it is particularly desired to introduce a carboxyl group into the polyurethane resin, amino acids such as glycine and L-alanine can be used as a reaction stopping agent. These terminal blocking agents can be used alone or in combination of two or more.
[0026] The reaction between the polyester polyol resin and the isocyanate compound and the amine compound can be carried out by a known method.
[0027] The content of the ortho-oriented aromatic dicarboxylic acid or its anhydride in the amorphous polyester resin (A) or the amorphous polyester urethane resin (B) relative to the total polyvalent carboxylic acid components is preferably 50 to 100% by mass. If it is within this range, favorable gas barrier properties can be exhibited. Among them, 70 to 100% by mass is more preferable.
[0028] The number average molecular weight of the amorphous polyester resin (A) and the amorphous polyurethane resin (B) is preferably 450 to 100,000, more preferably 3,000 to 50,000, and even more preferably 5,000 to 30,000.
[0029] When the number average molecular weight of the amorphous polyester resin (A) or the amorphous polyester urethane resin (B) is less than 450, the blocking resistance of the resulting ink composition and the strength and oil resistance of the printed film tend to be low, whereas when it exceeds 100,000, the viscosity of the resulting ink composition tends to be high and the gloss of the printed film tends to be low. The resin structure may be either a straight-chain or branched structure.
[0030] The content of the amorphous polyester resin (A) and / or amorphous polyester urethane resin (B) in the ink composition of the present invention is preferably 1% by weight or more based on the total weight of the non-volatile parts of the ink components from the viewpoint of sufficient adhesion of the ink to the printed substrate, and is preferably 80% by weight or less from the viewpoint of appropriate ink viscosity and work efficiency during ink production and printing, more preferably in the range of 3 to 70% by weight, and more preferably 10 to 60%.
[0031] The amorphous polyester resin (A) or amorphous polyester urethane resin (B) is used as the main resin in the ink composition of the present invention, but in order to further improve the blocking resistance, scratch resistance, heat resistance including retort and boiling suitability, adhesion, and laminate strength, a known resin (C) having a Tg or softening point of 40°C or more is used in combination within a range that does not impair the gas barrier property. By using a resin (C) having a Tg or softening point of 40°C or more in combination, excellent blocking resistance can be obtained without containing silica or silicone, and deterioration of the appearance after lamination can be prevented. Preferably, the Tg or softening point is 50°C or more, and more preferably 60°C or more.
[0032] The resin (C) having a Tg or softening point of 40° C. or higher is preferably a resin that does not improve or deteriorate the gas barrier property, and examples thereof include ethylene-vinyl acetate copolymer resin, ethylene vinyl alcohol resin, polyvinyl alcohol resin, vinyl acetate resin, cellulose resin, nitrocellulose resin, cellulose acetate propionate, cellulose acetate butyrate, polyamide resin, acrylic resin, polyester resin, alkyd resin, rosin resin, rosin-modified maleic acid resin, ketone resin (ketone-aldehyde resin), cyclized rubber, chlorinated rubber, butyral, and petroleum resin. The co-used resin may be used alone or in a mixture of two or more kinds. In order to improve blocking resistance and scratch resistance, cellulose acetate propionate (C1) and / or cellulose acetate butyrate (C2) are particularly preferred. Furthermore, in order to improve adhesion to the substrate, it is preferable to use a ketone resin-aldehyde resin (C3), a hydrogenated ketone-aldehyde resin (C4), or a urethane compound (C5) consisting of a ketone-aldehyde resin (C4) and an organic diisocyanate, or to use a rosin resin or a rosin-modified maleic acid resin. In addition, in the case of a water-based ink composition, an ethylene vinyl alcohol resin, a polyvinyl alcohol resin, or a polyvinyl acetal resin is preferable.
[0033] The content of the resin (C) having a Tg or softening point of 40° C. or higher is preferably 0.1 to 25% by weight, more preferably 0.1 to 15% by weight, and even more preferably 1.0 to 5.0% by weight, based on the total weight of the non-volatile matters of the ink components.
[0034] (Cellulose acetate propionate resin (C1) and cellulose acetate butyrate (C2)) The cellulose acetate propionate resin (C1) and cellulose acetate butyrate (C2) will be described.
[0035] The cellulose acetate alkylate resin used in the binder of the present invention is cellulose acetate butyrate resin (CAB) (C2) or cellulose acetate propionate resin (CAP) (C1), which can be used alone or in combination. Cellulose acetate propionate (C1) and cellulose acetate butyrate (C2) are obtained by the reaction of cellulose with an organic acid or anhydride. That is, cellulose is mixed with an organic acid, anhydride, and a catalyst, and reacted until a triester is formed. After complete acylation, the cellulose is hydrolyzed to obtain the desired hydroxyl group level. Cellulose acetate propionate (C1) is obtained by triesterification with acetic acid and propionic acid, followed by hydrolysis. Generally, resins with 0.6-2.5% acetylation by weight, 42-46% propionation by weight, and 1.8-5% hydroxyl groups are commercially available. From the viewpoint of compatibility with the polyurethane resin of the present invention, cellulose acetate propionate resin is more preferable, and has a propionyl group content of 40 to 50% by weight (median value 45%), an acetyl group content of 0.5 to 3% by weight (median value 2.5%), a hydroxyl group content of 2 to 6% by weight (median value 2.5%), and a viscosity of 0.05 to 0.2 Pa·s (ASTM Method D1343). Cellulose acetate butyrate (C2) is obtained by triesterification with acetic acid and butyric acid, followed by hydrolysis. Generally, resins with 2 to 30% by weight of acetylation, 17 to 53% by weight of butyrylation, and 1 to 5% of hydroxyl groups are commercially available.
[0036] (Ketone-aldehyde resin (C3)) The ketone-aldehyde resin (C43) that can be used in the present invention can be produced by a known method, and the production method is not particularly limited. The ketones that are components of the ketone-aldehyde resin are selected from aromatic, aliphatic, and alicyclic ketones. Examples include acetophenone, cyclohexanone, methylcyclohexanone, methyl ethyl ketone, and methyl isobutyl ketone. The aldehydes that are components of the ketone-aldehyde resin are selected from aromatic and aliphatic aldehydes. Examples include formaldehyde, acetaldehyde, butylaldehyde, dodecanal, and benzaldehyde. The ketone-aldehyde resin is obtained by a condensation reaction of ketones and aldehydes. For example, acetophenone-formaldehyde resin is obtained by a condensation reaction of acetophenone and formaldehyde. The condensation reaction is usually carried out in the presence of an alkali catalyst such as sodium hydroxide at 60 to 90°C for 10 minutes to 3 hours. Ketone-aldehyde resins are also commercially available, for example, TEGО (registered trademark) Variplus AP manufactured by EVONIK.
[0037] (Hydrogenated Ketone-Aldehyde Resins (C4)) The hydrogenated ketone-aldehyde resin is a resin having a structure in which a ketone group is converted to a hydroxyl group. The method of hydrogenating the ketone-aldehyde resin is not particularly limited. Examples of the method of hydrogenating the carbon-oxygen unsaturated bond of the ketone-aldehyde resin include general methods such as lithium aluminum hydride reduction, Meerwein-Ponndorf reduction, and catalytic reduction. Hydrogenated ketone-aldehyde resins are commercially available, such as TEGO (registered trademark) Variplus SK manufactured by EVONIK.
[0038] The number average molecular weight of the ketone-aldehyde resin (C3) or the hydrogenated ketone-aldehyde resin (C4) is usually preferably 500 to 1500, more preferably 700 to 900. If the molecular weight is less than 500, the drying property and blocking resistance decrease, and if it exceeds 1500, the solubility decreases and the printability tends to deteriorate.
[0039] (Hydrogenated ketone-aldehyde resin (C4) and urethane compound (C5) made of organic diisocyanate) The urethane compound (C5) containing the hydrogenated ketone-aldehyde resin usable in the present invention can be produced by a conventionally known method, and the production method is not particularly limited. For example, the hydroxyl group of the hydrogenated ketone-aldehyde resin (C4a) is reacted with an organic diisocyanate compound in a molar ratio in which the isocyanate group is in excess to synthesize a urethane compound. As the solvent, ester solvents such as ethyl acetate, propyl acetate, and butyl acetate, which are usually used as solvents for non-toluene gravure inks; ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; alcohol solvents such as methanol, ethanol, isopropyl alcohol, isopropyl alcohol, and n-butanol; and hydrocarbon solvents such as methylcyclohexane and ethylcyclohexane can be used alone or in mixtures of two or more of them. The reaction temperature is usually between 80°C and 200°C, and preferably between 90°C and 150°C. The urethane reaction is preferably carried out for 10 minutes to 5 hours, and the end point of the reaction is determined by viscosity measurement, NCO peak by IR measurement, NCO % measurement by titration, or the like.
[0040] Next, examples of the organic diisocyanate compounds that can be used include various known aromatic, aliphatic, or alicyclic diisocyanates, such as 1,5 naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl isocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, tolylene diisocyanate, butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, 2,2 These include 1,4-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, lysine diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, methylcyclohexane diisocyanate, norbornane diisocyanate, m-tetramethylxylylene diisocyanate, and dimer diisocyanate in which the carboxyl groups of dimer acid are converted into isocyanate groups.
[0041] The number average molecular weight of the urethane compound (C5) containing the hydrogenated ketone-aldehyde resin thus obtained as a component is preferably within the range of 1,000 to 3,000. If the number average molecular weight is less than 1,000, the blocking resistance in particular decreases, and if it exceeds 3,000, the long-term storage stability of the ink composition tends to decrease.
[0042] Furthermore, the urethane compound (C5) containing a hydrogenated ketone-aldehyde resin as a component that can be used in the present invention is commercially available, and examples thereof include TEGO (registered trademark) Variplus 1201TF manufactured by EVONIK.
[0043] (Chlorinated polyolefin resin (G)) The liquid printing ink of the present invention contains a chlorinated polyolefin resin (G). By containing a chlorinated polyolefin resin, the adhesion of the liquid printing ink to treated and untreated substrate films can be improved. In particular, since excellent adhesion can be obtained even to polyolefin-based films that tend to have poor adhesion, excellent adhesion can be realized regardless of the type of film.
[0044] The chlorinated polyolefin resin (G) may be any of various known chlorinated polyolefin resins, and is preferably one that dissolves in an organic solvent. The structure of the polyolefin resin in the chlorinated polyolefin resin is not particularly limited. For example, a resin containing a homopolymer or copolymer of an α-olefin-based unsaturated hydrocarbon such as polypropylene, poly-1-butene, or poly-4-methyl-1-pentene is preferred. Among them, one containing a polypropylene structure (i.e., a chlorinated polypropylene structure) is particularly preferred.
[0045] The chlorinated polyolefin resin (G) may be modified. The modified product is not particularly limited. For example, the modified chlorinated polyolefin is a chlorinated polyolefin graft-polymerized with a polymerizable acrylic compound (acrylic acid, methacrylic acid, or their alkyl esters, etc.) or an unsaturated polycarboxylic acid (maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, etc.), or a chlorinated polyolefin graft-polymerized with the unsaturated polycarboxylic acid.
[0046] The chlorination degree of the chlorinated polyolefin resin (G) is preferably 10% or more and 60% or less, more preferably 20% or more and 55% or less, and even more preferably 30% or more and 50% or less. When the chlorination degree is less than 10%, the solubility of the chlorinated polypropylene resin in a solvent tends to decrease. On the other hand, when the chlorination degree is more than 60%, the liquid printing ink tends to have a low adhesion to a substrate film such as polyethylene or polypropylene. When the chlorination degree is within the above range, the liquid printing ink can exhibit excellent adhesion to various films.
[0047] The weight average molecular weight of the chlorinated polyolefin resin (G) is preferably from 10000 to 60000, more preferably from 11000 to 50000, and further preferably from 12000 to 30000. A weight average molecular weight of 60000 or less is preferable because compatibility can be improved.
[0048] The content of the chlorinated polypropylene resin is preferably from 0.01 to 10% by mass, more preferably from 0.05 to 8% by mass, and even more preferably from 0.01 to 5% by mass, of the total amount of the liquid printing ink.
[0049] The liquid printing ink of the present invention is preferably free of vinyl chloride-based resins such as vinyl chloride-vinyl acetate copolymer resins and polyvinylidene chloride resins in organic solvent-based ink compositions, because vinyl chloride-based monomers have the detrimental effect of corroding recycling equipment.
[0050] In the liquid printing ink of the present invention, the chlorine-based resin component is preferably only the chlorinated polyolefin resin (G), and the chlorine content relative to the total weight of the non-volatile matters of the ink components is preferably 5 mass % or less, more preferably 1 mass % or less.
[0051] (Colorant (D)) The colorant (D) used in the present invention may be an organic or inorganic pigment or dye for the purpose of coloring, which is used in general inks, paints, and recording materials. Examples of organic pigments include azo-based, phthalocyanine-based, anthraquinone-based, perylene-based, perinone-based, quinacridone-based, thioindigo-based, dioxazine-based, isoindolinone-based, quinophthalone-based, azomethine azo-based, dictopyrrolopyrrole-based, and isoindoline-based pigments. It is preferable to use copper phthalocyanine for indigo ink and CI Pigment No. Yellow 83 for transparent yellow ink in terms of cost and light resistance.
[0052] Examples of inorganic pigments include carbon black, titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, red iron oxide, aluminum, and mica. In addition, a glittering pigment (Metashine; Nippon Sheet Glass Co., Ltd.) made of glass flakes or aggregate flakes as a base material and coated with a metal or metal oxide can be used. In terms of cost and coloring power, it is preferable to use titanium oxide for white ink, carbon black for black ink, aluminum for gold and silver ink, and mica for pearl ink. Aluminum is in powder or paste form, but it is preferable to use it in paste form from the standpoint of handling and safety, and whether to use leafing or non-leafing is appropriately selected from the standpoint of brightness and concentration.
[0053] The colorant (D) is preferably contained in an amount sufficient to ensure the concentration and coloring power of the ink, that is, in a ratio of 1 to 50% by weight based on the total weight of the non-volatile content of the ink components. The colorant may be used alone or in combination of two or more kinds. In addition, for white ink, which is consumed the most, titanium oxide is more preferable among colorants (D) because the printing area is large and a large gas barrier layer can be provided.
[0054] In order to stably disperse the colorant (D), particularly the pigment, in an organic solvent, the above-mentioned resin alone can be used, but a dispersant can also be used in combination to further stably disperse the pigment. As the dispersant, anionic, nonionic, cationic, amphoteric, or other surfactants can be used. For example, comb-structured polymer compounds obtained by polyester addition to polyethyleneimine, or alkylamine derivatives of α-olefin maleic acid polymers, can be mentioned. Specific examples include the Solspers series (ZENECA), Ajisper series (Ajinomoto), and Homogenol series (Kao). In addition, the BYK series (BYK-Chemie), EFKA series (EFKA), and the like can be appropriately used. The dispersant is preferably contained in the ink in an amount of 0.05% by weight or more based on the total weight of the nonvolatile content of the ink components from the viewpoint of storage stability of the ink, and 5% by weight or less from the viewpoint of lamination suitability, and more preferably in the range of 0.1 to 2% by weight.
[0055] (Organic solvent (E)) The organic solvent (E) used in the present invention for making the ink can be any solvent capable of dissolving the binder resin, but generally, organic solvents are preferred due to the problem of drying, and from the viewpoint of the recent working environment and safety, it is desirable not to use aromatic solvents such as toluene and xylene, or ketones such as acetone and methyl ethyl ketone. For example, ester solvents such as ethyl acetate, n-propyl acetate, butyl acetate, and propylene glycol monomethyl ether acetate, and alcohol solvents such as n-propanol, isopropanol, n-butanol, and propylene glycol monomethyl ether can be mentioned, and these can be used alone or in a mixture of two or more kinds. In particular, ethyl acetate and n-propyl acetate are preferred as the main solvent.
[0056] The liquid printing ink of the present invention may contain water as a volatile component together with the organic solvent. The content of water is preferably less than 10% by mass of the total amount of the ink composition. The addition of water can control the drying property of the ink, and in particular, in gravure printing, the gradation part with a small amount of ink transfer, which is a characteristic of gravure printing, can be beautifully reproduced. Furthermore, it is particularly preferable that the content of water is in the range of 1 to 5% by mass of the total amount of the ink composition for flexible packaging lamination, since this improves the printability.
[0057] In addition, the addition of water can reduce the amount of organic solvent used. Water may be added to the organic solvent in advance to form a water-containing mixed solvent, or a specific amount of water may be added separately.
[0058] The liquid printing ink of the present invention may also use an aqueous organic solvent. The aqueous organic solvent preferably contains water and an organic solvent miscible with water. Examples of the organic solvent miscible with water include alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol, and n-propyl alcohol; polyhydric alcohols such as propylene glycol and glycerin; ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono n-propyl ether, and ethyl carbitol; and the like. These are preferably used alone or in combination of two or more.
[0059] (Polyisocyanate (H)) In the present invention, polyisocyanate (H) may be used as a curing agent. The polyisocyanate (H) used in the present invention functions as a curing agent and reacts with the hydroxyl groups and amino groups of the amorphous polyester resin (A) and / or the amorphous polyester urethane resin (B) and resin (C) used in the ink composition of the present invention to give a three-dimensional crosslinked structure. Among them, polyisocyanate (H) is preferably a divalent or higher polyisocyanate compound (H-1) having an aromatic ring in the molecule.
[0060] (Divalent or higher polyisocyanate compound (H-1) having an aromatic ring in the molecule) The divalent or higher polyisocyanate compound (H-1) having an aromatic ring in the molecule is not particularly limited, and known compounds can be used. For example, at least one diisocyanate selected from xylylene diisocyanate, metaxylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and methylphenylethane diisocyanate, reaction products of the diisocyanate with a monovalent alcohol, reaction products of the diisocyanate with an alcohol having two hydroxyl groups, and carbodiimide modified products can be mentioned.
[0061] Examples of the trivalent or higher polyisocyanate compound include adducts which are reaction products of an excess amount of the diisocyanate with polyfunctional alcohols, such as low molecular weight active hydrogen compounds such as trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, diethanolamine, and triethanolamine, and alkylene oxide adducts thereof, various polyester resins, polyether polyols, and high molecular weight active hydrogen compounds such as polyamides, etc. Nurates which are polymers of the above diisocyanates can also be preferably used.
[0062] Among these, meta-xylylene diisocyanate, xylylene diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate are preferred, and meta-xylylene diisocyanate is most preferred. Furthermore, the reaction products, modified products, and polymers of these isocyanate compounds may also be used.
[0063] (Polyisocyanate compounds that do not have an aromatic ring in the molecule) In the present invention, the divalent or higher polyisocyanate compound (H-1) having an aromatic ring in the molecule may be used in combination with a polyisocyanate compound having no aromatic ring in the molecule as a curing agent. Conventional polyisocyanates having an aromatic ring harden the cured coating film, making it difficult to obtain good adhesive strength, but the combined use of a polyisocyanate compound having no aromatic ring in the molecule, particularly a diisocyanate such as an allophanate, imparts flexibility to the coating film while maintaining barrier properties, improves adhesion to metal substrates such as aluminum foil, aluminum vapor deposition film, and transparent vapor deposition film, and also improves barrier properties.
[0064] Examples of the polyisocyanate compound not having an aromatic ring in the molecule used in the present invention include at least one diisocyanate selected from hexamethylene diisocyanate, isophorone diisocyanate, norbornane diisocyanate, meta-xylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated methylphenylethane diisocyanate, and hydrogenated naphthalene-1,5-diisocyanate, reaction products of such diisocyanates with monohydric alcohols, reaction products of such diisocyanates with alcohols having two hydroxyl groups, and carbodiimide modified products.
[0065] Examples of the trivalent or higher polyisocyanate compound include adducts which are reaction products of an excess amount of the diisocyanate with polyfunctional alcohols, such as low molecular weight active hydrogen compounds such as trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, diethanolamine, and triethanolamine, and alkylene oxide adducts thereof, various polyester resins, polyether polyols, and high molecular weight active hydrogen compounds such as polyamides, etc. Nurates which are polymers of the above diisocyanates can also be preferably used.
[0066] Among them, polyisocyanate compounds (H-2) having a cyclic skeleton and no aromatic ring in the molecule are preferred. Examples of the cyclic skeleton include an alicyclic skeleton and a nurate skeleton.
[0067] The polyisocyanate having an alicyclic skeleton is preferably isophorone diisocyanate, norbornane diisocyanate, hydrogenated metaxylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated methylphenylethane diisocyanate, or hydrogenated naphthalene-1,5-diisocyanate. The reaction products, modified products, and polymers of these isocyanate compounds may also be used. (Mixing ratio of divalent or higher polyisocyanate compound (H-1) having an aromatic ring in the molecule and polyisocyanate compound (H-2) having a cyclic skeleton and no aromatic ring in the molecule) The mixing ratio of the polyisocyanate compound (H-1) having an aromatic ring in the molecule and the polyisocyanate compound (H-2) having a cyclic skeleton and no aromatic ring in the molecule depends on the molecular weight or valence of each compound used, so it cannot be generally stated. Therefore, the mixing ratio of the polyisocyanate compound (H-1) having an aromatic ring in the molecule and the polyisocyanate compound (H-2) having no aromatic ring in the molecule is preferably in the range of 1:5 to 10:1, more preferably 1:3 to 5:1, in terms of isocyanate content.
[0068] (Mixing ratio of amorphous polyester resin (A) and / or amorphous polyester urethane resin (B) to polyisocyanate (H)) The amorphous polyester resin (A) and / or amorphous polyester urethane resin (B) and the polyisocyanate (H) are preferably blended such that the ratio of the hydroxyl group of the amorphous polyester resin (A) and / or amorphous polyester urethane resin (B) to the isocyanate group of the polyisocyanate (H) (OH / NCO, equivalent ratio) is 1 / 0.01 to 1 / 20 (equivalent ratio), more preferably 1 / 1.2 to 1 / 10, and even more preferably 1 / 1.1 to 1 / 7 (Uchida confirmation). By blending the polyisocyanate (H), the adhesion of the ink to the substrate, the heat resistance during boiling or retort treatment, and the oxygen barrier property are improved. If the amount of the polyisocyanate (H) is excessive and exceeds the range, the excess polyisocyanate (H) may remain and bleed out from the adhesive layer after adhesion.
[0069] (Other Ingredients) The ink composition of the present invention may contain various additives within the range that does not impair the effects of the present invention. Examples of additives include extender pigments, leveling agents, defoamers, waxes, plasticizers, infrared absorbing agents, ultraviolet absorbing agents, antioxidants, heat stabilizers, fragrances, flame retardants, antistatic agents, lubricants, antiblocking agents, coupling agents, etc. When silica or silicone, which is a common antiblocking agent, is contained, the appearance after lamination tends to be poor, so it is preferable to have a composition that does not contain silica or silicone.
[0070] (Plate-shaped inorganic compound) The ink composition of the present invention may contain a plate-like inorganic compound for the purpose of imparting a higher gas barrier function. When a plate-like inorganic compound is used in combination, the plate-like shape is characterized by improved laminate strength and barrier properties. Examples of the plate-like inorganic compounds used in the present invention include hydrated silicates (phyllosilicate minerals, etc.), kaolinite-serpentine clay minerals (halloysite, kaolinite, endelite, dickite, nacrite, etc., antigorite, chrysotile, etc.), pyrophyllite-talc (pyrophyllite, talc, keroli, etc.), smectite clay minerals (montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, stevensite, etc.), vermiculite clay minerals (vermiculite, etc.), mica or mica clay minerals (muscovite, phlogopite, etc., mica, margarite, tetrasilylic mica, taeniolite, etc.), chlorite (cookite, sudoite, clinochlore, chamosite, nimite, etc.), hydrotalcite, plate-like barium sulfate, boehmite, aluminum polyphosphate, etc. These minerals may be natural clay minerals or synthetic clay minerals.
[0071] The charge between layers does not directly affect the barrier properties, but when the solvent is an organic solvent, the dispersibility in the resin is significantly inferior for ionic inorganic compounds, and increasing the amount added causes problems with printability (becoming thixotropic). In contrast, when the amount added is increased in the case of no charge, printability can be ensured. Regarding the particle size, a particle larger than about 1 μm is more likely to exhibit barrier properties, and good barrier properties cannot be obtained at the nm level. If the particle size is too large, in the case of gravure printing, etc., the plate-like inorganic compound does not enter the gravure plate, so printability cannot be obtained. The particle size is preferably 0.1 to 100 μm. More preferably, it is 1 to 40 μm. In the present invention, the average particle size means the particle size that appears most frequently when the particle size distribution of a certain plate-like inorganic compound is measured using a light scattering measuring device.
[0072] The aspect ratio of the plate-like inorganic compound used in the present invention is preferably high in order to improve the barrier function due to the labyrinth effect of gas component molecules. Specifically, it is preferably 3 or more, more preferably 10 or more, and most preferably 50 or more. The content of the plate-like inorganic compound is optional, but is preferably 50% by mass or less in the solid content. If it exceeds 50% by mass, the printability and appearance may be insufficient.
[0073] The ink composition of the present invention is characterized by the resin having a barrier property, and can also be used as a nearly transparent medium or extender for adjusting color density without using a colorant. For the purpose of preventing blocking, it is preferable to use an inorganic pigment, and from the viewpoint of not coloring, barium sulfate, calcium carbonate, silica, and mica are preferable. Moreover, from the viewpoint of improving the barrier property, the plate-like inorganic compounds such as mica are more preferable.
[0074] For printed items that are mostly plain, barrier properties can be imparted to the packaging material by printing the above medium and extender over the entire surface of the base material.
[0075] (Manufacturing method) The ink composition of the present invention can be produced by dissolving and / or dispersing a resin, a colorant, etc. in a solvent. Specifically, a pigment dispersion is produced by dispersing a pigment, etc. in an organic solvent with an amorphous polyester resin (A) and / or an amorphous polyester urethane resin (B), and other compounds, etc. are blended with the obtained pigment dispersion as necessary to produce an ink.
[0076] The particle size distribution of the pigment in the pigment dispersion can be adjusted by appropriately adjusting the size of the grinding media of the dispersing machine, the packing rate of the grinding media, the dispersion treatment time, the discharge speed of the pigment dispersion, the viscosity of the pigment dispersion, etc. As the dispersing machine, for example, a commonly used roller mill, ball mill, pebble mill, attritor, sand mill, etc. can be used.
[0077] When air bubbles or unexpectedly large particles are contained in the ink, they degrade the quality of the printed matter, so it is preferable to remove them by filtration, etc. As the filter, a conventionally known filter can be used.
[0078] The viscosity of the ink produced by the above method is preferably in the range of 10 mPa s or more from the viewpoint of preventing sedimentation of the pigment and adequately dispersing it, and 1000 mPa s or less from the viewpoint of workability during ink production and printing. The above viscosity is measured at 25°C using a Tokimec B-type viscometer.
[0079] The viscosity of the ink can be adjusted by appropriately selecting the types and amounts of raw materials used, such as polyurethane resin, colorant, organic solvent, etc. The viscosity of the ink can also be adjusted by adjusting the particle size and particle size distribution of the pigment in the ink.
[0080] The hues of the ink of the present invention are five process basic colors, yellow, red, indigo, black, and white, depending on the type of colorant used, and three process gamut colors, red (orange), grass (green), and purple. In addition, transparent yellow, peony, vermilion, brown, gold, silver, pearl, and a nearly transparent medium (containing an extender pigment as necessary) for adjusting color density are prepared as base colors. Inks for boiling retort are appropriately selected in consideration of the migration property and heat resistance of the pigment. The base inks of each hue are diluted with a diluting solvent to a viscosity and concentration suitable for gravure printing, and are supplied to each printing unit alone or mixed together.
[0081] (Printed material) The printed matter of the present invention is a printed matter comprising a substrate and a printed layer formed by printing the ink composition of the present invention on the substrate and then curing the printed layer.
[0082] The substrate can be any of various plastic films known as soft packaging materials, specifically, films or sheets made of polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate (hereinafter also referred to as PET), polycarbonate, and polylactic acid, polystyrene-based resins such as AS resin and ABS resin, nylon, polyamide, polyvinyl chloride, polyvinylidene chloride, cellophane, paper, aluminum, or composite materials thereof. Vapor-deposited films obtained by vapor-depositing metals or metal oxides onto the above-mentioned plastic films can also be used. In recent years, in order to improve the recycling efficiency of packaging materials, there has been active development of olefin-based mono-material packages using a substrate made only of polypropylene or polyethylene. The barrier white ink of the present invention can compensate for the oxygen barrier, which is a weakness of olefin-based mono-materials, so polyethylene and polypropylene films are suitable from the viewpoint of improving recyclability.
[0083] It is also preferable to use a film formed from a material containing a biomass-derived component as the film substrate. Biomass films are sold by various companies, and for example, sheets such as those listed in the list of biomass certified products listed in the Japan Organics Resources Association can be used.
[0084] Specifically, a well-known film is made from biomass-derived ethylene glycol. Biomass-derived ethylene glycol is made from ethanol (biomass ethanol) produced from biomass. For example, biomass-derived ethylene glycol can be obtained by a method of producing ethylene glycol from biomass ethanol via ethylene oxide using a conventionally known method. Commercially available biomass ethylene glycol may also be used, and for example, biomass ethylene glycol commercially available from India Glycoal Limited can be suitably used.
[0085] Alternatively, products using biomass raw materials classified by the degree of biomass plastic as stipulated by ISO16620 or ASTM D6866 are also on the market. Radioactive carbon-14C exists in the atmosphere at a ratio of 1 in 1012 particles, and this ratio does not change even with atmospheric carbon dioxide, so this ratio does not change even in plants that fix this carbon dioxide through photosynthesis. For this reason, the carbon in plant-derived resins contains radioactive carbon-14C. In contrast, the carbon in fossil fuel-derived resins contains almost no radioactive carbon-14C. Therefore, by measuring the concentration of radioactive carbon-14C in the resin with an accelerator mass spectrometer, the proportion of plant-derived resin in the resin, i.e., the degree of biomass plastic, can be determined. Examples of plant-derived low-density polyethylene, which is a biomass plastic having a biomass plastic content of 80% or more, preferably 90% or more as specified by ISO16620 or ASTM D6866, include Braskem products under the trade names "SBC818", "SPB608", "SBF0323HC", "STN7006", "SEB853", and "SPB681", and films using these as raw materials can be preferably used.
[0086] For example, as an alternative to conventional polyethylene terephthalate films using petroleum-based raw materials, films containing biomass polyesters and biomass polyethylene terephthalate, which have biomass-derived ethylene glycol as the diol unit and fossil fuel-derived dicarboxylic acids as the dicarboxylic acid units, are known. The dicarboxylic acid unit of the biomass polyester uses a dicarboxylic acid derived from a fossil fuel. As the dicarboxylic acid, an aromatic dicarboxylic acid, an aliphatic dicarboxylic acid, and a derivative thereof can be used without limitation.
[0087] In addition to the above diol component and dicarboxylic acid component, the copolymer polyester may be a copolymer polyester containing a copolymer component as a third component, such as a bifunctional oxycarboxylic acid or at least one polyfunctional compound selected from the group consisting of a trifunctional or higher functional polyhydric alcohol, a trifunctional or higher functional polycarboxylic acid and / or its anhydride, and a trifunctional or higher functional oxycarboxylic acid, in order to form a crosslinked structure.
[0088] In addition, for example, as an alternative to conventional polyolefin films using petroleum-based raw materials, biomass polyolefin films such as biomass polyethylene films and biomass polyethylene-polypropylene films, which contain polyethylene resins made from biomass-derived ethylene glycol, are also known.
[0089] The polyethylene resin is not particularly limited except that ethylene glycol derived from biomass is used as part of the raw material. Examples of the polyethylene resin include ethylene homopolymers and copolymers of ethylene and α-olefins with ethylene as the main component (ethylene-α-olefin copolymers containing 90% by mass or more of ethylene units). These may be used alone or in combination of two or more.
[0090] The α-olefin constituting the copolymer of ethylene and α-olefin is not particularly limited, and examples thereof include α-olefins having 4 to 8 carbon atoms, such as 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Known polyethylene resins, such as low-density polyethylene resin, medium-density polyethylene resin, and linear low-density polyethylene resin, can be used.
[0091] Among these, from the viewpoint of making it more difficult for damage such as holes or tears to occur even when films are rubbed against each other, linear low-density polyethylene resin (LLDPE) (a copolymer of ethylene and 1-hexene, or a copolymer of ethylene and 1-octene) is preferred, and linear low-density polyethylene resin having a density of 0.910 to 0.925 g / cm3 is more preferred.
[0092] In addition, films and sheets containing starch, a biomass raw material, or polylactic acid are also known. These can be selected and used appropriately depending on the application.
[0093] The biomass film may be a laminate of a plurality of biomass films, or may be a laminate of a conventional petroleum-based film and a biomass film.
[0094] These petroleum-based films and biomass films may be laminated with a vapor-deposited layer of a metal such as aluminum or a metal oxide such as silica or alumina, may use a metal foil, may be used in combination with a barrier film containing a gas barrier layer such as polyvinyl alcohol, an ethylene-vinyl alcohol copolymer, or vinylidene chloride, or may be coated with polyvinyl alcohol, etc. By using such a film, a laminate with higher barrier properties against water vapor, oxygen, alcohol, inert gases, volatile organic compounds (fragrances), etc. can be obtained.
[0095] These films may be unstretched or stretched, and the manufacturing method is not limited. As a stretching method, a resin is melt-extruded into a sheet by an extrusion film forming method or the like, and then simultaneous biaxial stretching or sequential biaxial stretching is generally performed. In the case of sequential biaxial stretching, a longitudinal stretching process is generally performed first, and then a transverse stretching process is generally performed. Specifically, a method of combining longitudinal stretching utilizing the speed difference between rolls and transverse stretching using a tenter is often used.
[0096] The thickness of the base film is not particularly limited, but is usually in the range of 1 to 500 μm. The film surface may be subjected to various surface treatments such as flame treatment and corona discharge treatment as necessary so that an adhesive layer without defects such as film breakage or repellency is formed.
[0097] The paper can be made of any known paper base material without any particular limitation. Specifically, the paper is made by a known paper machine using natural fibers for papermaking such as wood pulp, but the papermaking conditions are not particularly specified. Examples of natural fibers for papermaking include wood pulp such as softwood pulp and hardwood pulp, non-wood pulp such as Manila hemp pulp, sisal hemp pulp, and flax pulp, and pulps obtained by chemically modifying these pulps. As the type of pulp, chemical pulp, ground pulp, chemi-ground pulp, thermomechanical pulp, etc., made by sulfate cooking method, acidic / neutral / alkaline sulfite cooking method, soda salt cooking method, etc., can be used. In addition, various commercially available papers used for cosmetics, beverages, medicines, toys, equipment, etc., such as fine paper, craft paper, pure white roll paper, glassine paper, parchment paper, manila cardboard, white cardboard, coated paper, art paper, imitation paper, lined paper, impregnated paper, cardboard, paperboard, thin paper, thick paper, and polyethylene-coated paper, can also be used.
[0098] The printing method can be a known printing method such as gravure printing or flexographic printing, but gravure printing is particularly preferred. The cylinder used for gravure printing is a known type such as an engraved type or an etched type. A printed matter can be obtained by applying the ink using the printing method described above and then drying or curing it in an oven to fix it. The substrate may be subjected to a deposition coating treatment of a metal oxide or the like and / or a coating treatment of polyvinyl alcohol or the like on the surface, and may further be subjected to a surface treatment such as a corona treatment.
[0099] The ink composition of the present invention can be preferably used as a surface printing ink, a reverse printing ink, or a lamination ink. When used as a surface printing ink, an overprint varnish layer can be provided separately. On the other hand, when used as a reverse printing ink, an anchor coat varnish layer can be provided separately. In addition, it is preferable to print on a film having gas barrier properties, such as a film laminated with a plastic film such as an ethylene-vinyl alcohol copolymer or polyvinyl alcohol having gas barrier properties, a vapor deposition film in which a metal or metal oxide is vapor-deposited, a film using a metal foil, or a film laminated with an adhesive having a gas barrier function as the adhesive of the film, since a synergistic effect of the gas barrier properties can be expected.
[0100] (Laminate) The laminate of the present invention is obtained by laminating a plurality of substrates, and has a printed layer of the liquid ink composition of the present invention on at least one of the substrates. The substrates can be laminated by bonding with an adhesive or by extrusion lamination. The substrates can be the same as those described for the printed matter above.
[0101] More specifically, the laminate has the following structure: (1) Base film 1 / printing layer / adhesive layer 1 / sealant film (2) Base film 1 / printed layer / adhesive layer 1 / metal-deposited unstretched film (3) Base film 1 / printed layer / adhesive layer 1 / metal-deposited stretched film (4) Transparent vapor-deposited stretched film / printed layer / adhesive layer 1 / sealant film (5) Base film 1 / printing layer / adhesive layer 1 / base film 2 / adhesive layer 2 / sealant film (6) Base film 1 / printed layer / adhesive layer 1 / metal-deposited stretched film / adhesive layer 2 / sealant film (7) Base film 1 / printed layer / adhesive layer 1 / transparent vapor-deposited stretched film / adhesive layer 2 / sealant film (8) Base film 1 / printed layer / adhesive layer 1 / metal layer / adhesive layer 2 / sealant film (9) Base film 1 / printing layer / adhesive layer 1 / base film 2 / adhesive layer 2 / metal layer / adhesive layer 3 / sealant film (10) Base film 1 / printed layer / adhesive layer 1 / metal layer / adhesive layer 2 / base film 2 / adhesive layer 3 / sealant film Examples include, but are not limited to, the following. The "printed layer" here refers to the printed layer of the liquid ink composition of the present invention. In the above configurations (1) to (10), a printed layer is provided on the adhesive layer 1 side of the substrate film 1, but a printed layer may be provided on the surface (front surface) of the substrate film 1 opposite to the adhesive layer 1, or a printed layer may be provided on the substrate film 2. In the above configurations (1) to (10), a laminate is formed by laminating the substrate film 1 and the substrate film 2 or the sealant film via the adhesive layer 1 or the adhesive layer 2, but an extrusion lamination configuration may be used in which a molten resin is extruded without providing the adhesive layer 1 or the adhesive layer 2. In the case of extrusion lamination, it is preferable to use polyethylene or polypropylene as the extrusion resin. In that case, an imine-based, butadiene-based, or isocyanate-based anchor coat layer may be provided on the printed layer, and the resin may be melt-extruded on the anchor coat layer.
[0102] The laminate of the present invention may also have a removable primer layer as a layer in contact with the printed layer or the adhesive layer. By having a removable primer layer, peeling of the printed layer or peeling of multiple films can be facilitated, the recyclability of the film can be improved, and the quality of the recycled plastic can be improved.
[0103] The primer layer is preferably a film that can be detached from the substrate by treatment with an alkaline solution, for example. A known layer can be used as the layer that can be detached from the substrate by treatment with an alkaline solution, and for example, it can be dissolved or swelled by hydrolysis in an alkaline solution, and can be detached from the substrate. As long as a film that can be detached from the substrate by treatment with an alkaline solution can be formed, the type of primer layer forming composition that forms the primer layer is not particularly limited, but for example, a composition containing a urethane resin or polyvinyl alcohol is preferred, or a composition containing a resin having an acidic group is also preferred.
[0104] Examples of the resin having an acidic group include resins having an acid value, such as polyurethane resins having an acid value, rosin-modified maleic acid resins and rosin-modified fumaric acid resins; radical copolymer resins such as (meth)acrylic resins, styrene-(meth)acrylic resins, styrene-maleic acid (anhydride) resins and terpene-maleic acid (anhydride) resins, which are copolymerized with polymerizable monomers having an acidic group, such as polymerizable monomers having a carboxyl group, such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, cinnamic acid, or acid anhydrides thereof, polymerizable monomers having a sulfonic acid group, such as sulfonated styrene, and polymerizable monomers having a sulfonamide group, such as vinylbenzenesulfonamide; and acid-modified polyolefin resins, which may be used singly or in combination.
[0105] The composition for forming a primer layer may contain, in addition to the above-mentioned resin, a solvent such as an organic solvent or an aqueous solvent, an additive, etc. Examples of the additive include the same auxiliary agent and acidic additive that can be added to the composition for forming an ink layer described above.
[0106] Examples of the base film 1 used in the structure (1) include an OPP film, a PET film, and a nylon film (hereinafter also referred to as an Ny film). The base film 1 may be coated with a coating for the purpose of improving the gas barrier properties and the ink receptivity when a printing layer is provided, which will be described later. Examples of commercially available base films 1 with coatings include K-OPP films and K-PET films. Examples of sealant films include CPP films and LLDPE films.
[0107] The base film 1 used in the structures (2) and (3) can be an OPP film, a PET film, etc. As the metal-vapor-deposited unstretched film, a VM-CPP film obtained by depositing a metal such as aluminum on a CPP film can be used, and as the metal-vapor-deposited stretched film, a VM-OPP film obtained by depositing a metal such as aluminum on an OPP film can be used.
[0108] Examples of the transparent evaporated stretched film used in the structure (4) include films obtained by evaporating silica or alumina onto OPP film, PET film, nylon film, etc. For the purpose of protecting the inorganic evaporated layer of silica or alumina, a film having a coating applied onto the evaporated layer may be used. Examples of the sealant film include the same as those in the structure (1).
[0109] The base film 1 used in the structure (5) may be a PET film, etc. The base film 2 may be a nylon film, etc. The sealant film may be the same as that in the structure (1).
[0110] The base film 1 of the structure (6) may be the same as that of the structures (2) and (3). The metal-vapor-deposited stretched film may be a VM-OPP film or a VM-PET film in which a metal such as aluminum is vapor-deposited on an OPP film or a PET film. The sealant film may be the same as that of the structure (1).
[0111] The base film 1 in the structure (7) may be a PET film, etc. The transparent deposition stretched film may be the same as that in the structure (4). The sealant film may be the same as that in the structure (1).
[0112] The base film 1 in the structure (8) may be a PET film, etc. The metal layer may be an aluminum foil, etc. The sealant film may be the same as that in the structure (1).
[0113] In the structures (9) and (10), the base film 1 may be a PET film or the like. The base film 2 may be a nylon film or the like. The metal layer may be an aluminum foil or the like. The sealant film may be the same as that in the structure (1).
[0114] (Adhesive layer) The adhesive used in the adhesive layer may be any known adhesive for film lamination, but it is preferable to use an adhesive having gas barrier properties as the adhesive, since this can provide a laminate with particularly excellent barrier properties. 2 The oxygen barrier property of the cured coating of the adhesive applied at (solid content) is 300cc / m 2 / day / atm or less, or water vapor barrier of 120g / m 2 / day This refers to a product that satisfies at least one of the following conditions. Commercially available products include the "PASLIM" series, such as PASLIM VM001 / 108CP, PASLIM MB100A / MB-520B, and PASLIM J350X manufactured by DIC Corporation, and "Maxive" manufactured by Mitsubishi Gas Chemical Company.
[0115] The adhesive layer may be made of any known material without particular limitation, but preferably contains a cured product of a polyol and an isocyanate compound. When the polyol and / or isocyanate compound contains a biomass-derived component, a laminate with a high biomass content can be obtained, thereby reducing the environmental load.
[0116] From the viewpoints of gas barrier properties and adhesive properties, the cured product of a polyol and an isocyanate compound can preferably be a two-component adhesive comprising, for example, a polyol composition (A) containing at least one polyester polyol of the following (A1) to (A5) and a polyisocyanate composition (B) containing a compound having at least two isocyanate groups in one molecule (hereinafter also simply referred to as an isocyanate compound). (1) Polyester polyol (A1) obtained by reacting a polyester polyol having three or more hydroxyl groups with a carboxylic acid anhydride or a polycarboxylic acid. (2) Polyester polyol having polymerizable carbon-carbon double bonds (A2) (3) Polyester polyol having a glycerol skeleton (A3) (4) Polyester polyol (A4) obtained by polycondensation of ortho-oriented polycarboxylic acid and polyhydric alcohol (5) Polyester polyol having an isocyanuric ring (A5) The hydroxyl value of the polyester polyol is preferably 20 mgKOH / g or more and 250 mgKOH / g or less. When the polyester polyol has an acid group, the acid value is preferably 200 mgKOH / g or less. The lower limit of the acid value of the polyester polyol is not particularly limited, but is, for example, 20 mgKOH / g or more. The hydroxyl value of the polyester polyol can be measured by the hydroxyl value measurement method described in JIS-K0070, and the acid value can be measured by the acid value measurement method described in JIS-K0070.
[0117] The number average molecular weight of the polyester polyol is particularly preferably 300 to 5000, since a crosslinking density that provides an excellent balance between adhesiveness and gas barrier properties can be obtained. More preferably, the number average molecular weight is 350 to 3000. The number average molecular weight is calculated from the obtained hydroxyl value and the number of functional groups of the designed hydroxyl group. The glass transition temperature of the polyester polyol is preferably -30°C or higher and 80°C or lower, more preferably 0°C or higher and 60°C or lower, and even more preferably 25°C or higher and 60°C or lower.
[0118] The polyester polyol may be a polyester polyurethane polyol obtained by reacting the polyester polyols (A1) to (A5) with a diisocyanate compound to undergo urethane elongation to give a number average molecular weight of 1000 to 15000. The urethane-elongated polyester polyol contains a molecular weight component and urethane bonds of a certain level or more, and therefore has excellent gas barrier properties, excellent initial cohesive strength, and is excellent as an adhesive for lamination.
[0119] The polyisocyanate composition (B), which is one component of the two-component adhesive having gas barrier properties, contains an isocyanate compound. The isocyanate compound may be any of the conventionally known compounds without any particular limitation. Examples of the isocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, or dimers and trimers of these isocyanate compounds, and adducts obtained by reacting an excess amount of these isocyanate compounds with low molecular weight active hydrogen compounds such as ethylene glycol, propylene glycol, meta-xylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and meta-xylylenediamine, and alkylene oxide adducts thereof, various polyester resins, polyether polyols, and polymeric active hydrogen compounds such as polyamides. Polyester polyisocyanates obtained by reacting polyester polyols (A1) to (A5) with a diisocyanate compound in an isocyanate excess ratio between hydroxyl groups and isocyanate groups may be used. These may be used alone or in combination of two or more.
[0120] Also, blocked isocyanate may be used as the isocyanate compound. Examples of the isocyanate blocking agent include phenols such as phenol, thiophenol, methylthiophenol, ethylthiophenol, cresol, xylenol, resorcinol, nitrophenol, and chlorophenol, oximes such as acetoxime, methylethylketoxime, and cyclohexanoneoxime, alcohols such as methanol, ethanol, propanol, and butanol, halogen-substituted alcohols such as ethylene chlorohydrin and 1,3-dichloro-2-propanol, tertiary alcohols such as t-butanol and t-pentanol, lactams such as ε-caprolactam, δ-valerolactam, γ-butyrolactam, and β-propylolactam, and also include aromatic amines, imides, active methylene compounds such as acetylacetone, acetoacetate, and malonic acid ethyl ester, mercaptans, imines, ureas, diaryl compounds, and sodium bisulfite. The blocked isocyanate can be obtained by subjecting the above-mentioned isocyanate compound to an addition reaction with an isocyanate blocking agent by a known, conventional, appropriate method.
[0121] Among these, xylylene diisocyanate, hydrogenated xylylene diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate are preferred because they provide good gas barrier properties, and it is more preferred to use an isocyanate compound having a meta-xylene skeleton, such as meta-xylylene diisocyanate and meta-hydrogenated xylylene diisocyanate.
[0122] In addition, when a composition containing a polyester polyol having residual carboxylic acid groups such as polyester polyol (A1) is used as the polyol composition (A), the polyisocyanate composition (B) may contain a known epoxy compound. In addition, when a composition containing a polyol having a polymerizable carbon-carbon double bond such as polyester polyol (A2) is used, a known polymerization catalyst can be used in combination to promote polymerization of the carbon-carbon double bond, and for example, a known transition metal complex or photopolymerization initiator may be used in combination.
[0123] The polyol composition (A) and the polyisocyanate composition (B) are preferably mixed so that the equivalent ratio of the hydroxyl group contained in the polyol composition (A) to the isocyanate group contained in the polyisocyanate composition (B) is 1 / 0.5 to 1 / 10, and more preferably 1 / 1 to 1 / 5. If the isocyanate compound is excessive, the excess isocyanate compound remaining in the cured coating film of the adhesive may bleed out from the adhesive layer. On the other hand, if the reactive functional group contained in the polyisocyanate composition (B) is insufficient, the adhesive strength may be insufficient.
[0124] The gas barrier adhesive may contain various additives within a range that does not impair adhesion and gas barrier properties. For example, an inorganic filler may be used. Examples of inorganic fillers include silica, alumina, aluminum flakes, and glass flakes. In particular, it is preferable to use a plate-like inorganic compound as the inorganic filler, since it improves adhesive strength, gas barrier properties, light shielding properties, and the like. Examples of the plate-like inorganic compounds include hydrated silicates (phyllosilicate minerals, etc.), kaolinite-serpentine clay minerals (halloysite, kaolinite, endelite, dickite, nacrite, etc., antigorite, chrysotile, etc.), pyrophyllite-talc (pyrophyllite, talc, keroli, etc.), smectite clay minerals (montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, stevensite, etc.), vermiculite clay minerals (vermiculite, etc.), mica or mica clay minerals (muscovite, phlogopite, etc., mica, margarite, tetrasilylic mica, taeniolite, etc.), chlorite (cookite, sudoite, clinochlore, chamosite, nimite, etc.), hydrotalcite, plate-like barium sulfate, boehmite, aluminum polyphosphate, etc. These minerals may be natural clay minerals or synthetic clay minerals. The plate-like inorganic compounds can be used alone or in combination of two or more.
[0125] In addition, the adhesive may contain an adhesion promoter, an acid anhydride, a compound having an oxygen scavenging function, a tackifier, a gas barrier adhesive stabilizer (antioxidant, heat stabilizer, ultraviolet absorber, etc.), a plasticizer, an antistatic agent, a lubricant, an antiblocking agent, a colorant, a crystal nucleating agent, etc. These various additives may be added in advance to either one or both of the polyol composition (A) and the polyisocyanate composition (B), or may be added when the polyol composition (A) and the polyisocyanate composition (B) are mixed.
[0126] The gas barrier adhesive used may be either a solvent-based or solventless type. When the gas barrier adhesive used is a solvent-based adhesive, the adhesive of the present invention is applied onto the surface of the printed layer printed on the first substrate using a roll such as a gravure roll, and the organic solvent is evaporated by heating in an oven or the like, and then the other substrate is laminated to obtain the laminate of the present invention. After lamination, it is preferable to perform an aging treatment. The aging temperature is preferably room temperature to 80°C, and the aging time is preferably 12 to 240 hours.
[0127] When the gas barrier adhesive used is a solventless type, the adhesive of the present invention, which has been preheated to about 40°C to 100°C, is applied to the printed layer surface of the first substrate using a roll such as a gravure roll, and the other substrate is immediately laminated to obtain the laminate of the present invention. After lamination, it is preferable to carry out an aging treatment. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.
[0128] When the gas barrier adhesive is used as an adhesion promoter, the adhesion promoter of the present invention is applied to the printed layer surface printed on the first substrate using a roll such as a gravure roll, and the organic solvent is evaporated by heating in an oven or the like, and then the polymer material melted by an extruder is laminated to obtain the laminate of the present invention. As the polymer material to be melted, polyolefin resins such as low-density polyethylene resin, linear low-density polyethylene resin, and ethylene-vinyl acetate copolymer resin are preferred. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.
[0129] The amount of gas barrier adhesive to be applied is adjusted as appropriate. For example, in the case of a solvent-based adhesive, the solid content is 1 g / m 2 More than 10g / m 2 Less than 2 g / m 2 More than 5g / m 2 Adjust the amount of adhesive applied so that it is as follows: For a solvent-free adhesive, the amount of adhesive applied is, for example, 1 g / m 2 More than 5g / m 2 Less than 1 g / m 2 More than 3g / m 2 The following is the result.
[0130] When using an adhesive as an adhesive auxiliary, the amount of application is adjusted appropriately. For example, 2 More than 2g / m 2 The solid content is as follows: (Laminate other layers) The laminate of the present invention may be used alone or may further include other films or substrates. As the other substrates, in addition to the above-mentioned stretched film, unstretched film, and transparent vapor deposition film, porous substrates such as paper, wood, and leather can also be used. The adhesive used when bonding the other substrates may or may not be a gas barrier adhesive as described above.
[0131] <Packaging material> The printed matter and laminate of the present invention can be used as a multi-layer packaging material for the purpose of protecting food, medicines, etc. When used as a multi-layer packaging material, the layer structure can be changed depending on the contents, the environment of use, and the form of use.
[0132] The packaging material of the present invention can be obtained, for example, by using the laminate of the present invention, overlapping the surfaces of the sealant films of the laminate so that they face each other, and then heat-sealing the peripheral edge. Examples of the bag-making method include folding or overlapping the laminate of the present invention so that the surfaces of the inner layers (the surfaces of the sealant films) face each other, and heat-sealing the peripheral edge, for example, by a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type, a pleated seal type, a flat bottom seal type, a square bottom seal type, a gusset type, or other heat seal type. The packaging material of the present invention can take various forms depending on the contents, the environment of use, and the form of use. Self-supporting packaging materials (standing pouches) and the like are also possible. Heat sealing can be performed by known methods such as bar seal, rotary roll seal, belt seal, impulse seal, high frequency seal, and ultrasonic seal.
[0133] The packaging material of the present invention is filled with contents through its opening, and the opening is then heat-sealed to produce a product using the packaging material of the present invention.
[0134] The printed matter, laminate and packaging material of the present invention are recyclable. In particular, by configuring the ink composition constituting the printed layer to be free of vinyl chloride-vinyl acetate copolymer resin, polyvinylidene chloride resin or other vinyl chloride resin, corrosion of recycling equipment can be prevented, making it suitable for recyclability.
[0135] The method for recycling the printed matter, laminate and packaging material of the present invention is not particularly limited, and can be carried out using known methods and equipment. EXAMPLES
[0136] The present invention will be described more specifically with reference to examples. In the following, all "parts" and "%" are by weight.
[0137] (Production Example 1) Production method of polyester polyol resin (PE1) In a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 33.76 parts of ethylene glycol, 62.21 parts of phthalic anhydride, 15.36 parts of adipic acid, and 0.004 parts of titanium tetraisopropoxide were charged, and the inside temperature was maintained at 220° C. by gradually heating so that the temperature at the top of the rectification tube did not exceed 100° C. When the acid value became 0.5 mg KOH / g or less, the esterification reaction was terminated, and then 66.67 parts of ethyl acetate were charged to obtain a polyester solution PE1 having a number average molecular weight of 5000.
[0138] (Production Example 2) Production method of polyester polyol resin (PE2) In a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 33.39 parts of ethylene glycol, 62.56 parts of phthalic anhydride, 15.45 parts of adipic acid, and 0.004 parts of titanium tetraisopropoxide were charged, and the internal temperature was maintained at 220° C. by gradually heating so that the temperature at the top of the rectification tube did not exceed 100° C. When the acid value became 0.5 mg KOH / g or less, the esterification reaction was terminated, and then 66.67 parts of ethyl acetate were charged to obtain a polyester solution PE2 having a number average molecular weight of 9000.
[0139] (Production Example 3) Production method of polyester urethane resin (PEU31) Into a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 41.24 parts of ethylene glycol, 55.18 parts of phthalic anhydride, 13.63 parts of adipic acid, and 0.004 parts of titanium tetraisopropoxide were charged, and the inside temperature was maintained at 220° C. by gradually heating so that the temperature at the top of the rectification tube did not exceed 100° C. When the acid value became 0.5 mg KOH / g or less, the esterification reaction was terminated, and a polyester intermediate PE3 having a number average molecular weight of 500 was obtained.
[0140] Next, 72.44 parts of polyester polyol (PE3), 27.56 parts of isophorone diisocyanate, and 30 parts of ethyl acetate were charged into a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, and reacted at 70°C for 15 hours under a nitrogen stream, and then 36.67 parts of ethyl acetate were added to obtain a polyester urethane resin (PEU31). The obtained polyurethane resin solution (PEU31) had a resin solid concentration of 60% by weight.
[0141] (Production Example 4) Production method of polyester urethane resin (PEU32) In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, 71.07 parts of the polyester polyol (PE3) prepared in Production Example 3, 28.93 parts of isophorone diisocyanate, and 30 parts of ethyl acetate were charged and reacted at 70°C for 20 hours under a nitrogen stream, and then 36.67 parts of ethyl acetate were added to obtain a polyester urethane resin (PEU32). The resulting polyurethane resin solution (PEU32) had a resin solids concentration of 60% by weight.
[0142] (Production Example 5) Production method of polyester urethane resin (PEU33) In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, 69.87 parts of the polyester polyol (PE3) prepared in Production Example 3, 30.13 parts of isophorone diisocyanate, and 100.00 parts of ethyl acetate were charged and reacted at 70°C for 25 hours under a nitrogen stream, and then 133.33 parts of ethyl acetate was added to obtain a polyester urethane resin (PEU33). The obtained polyurethane resin solution (PEU33) had a resin solid concentration of 30% by weight.
[0143] (Production Example 6) Production method of polyester urethane resin (PEU34) In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube, 66.33 parts of polyester polyol (PE3) prepared in Production Example 3, 31.44 parts of isophorone diisocyanate and 40.00 parts of ethyl acetate were charged and reacted under a nitrogen stream at 70°C for 15 hours to produce a urethane prepolymer having an isocyanate group, and then 50.0 parts of ethyl acetate were added to the mixture to obtain a homogeneous solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 2.23 parts of isophorone diamine, 96.67 parts of ethyl acetate and 46.67 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45°C for 5 hours to obtain a polyester urethane resin (PEU34). The obtained polyurethane resin solution (PEU34) had a resin solids concentration of 30% by weight.
[0144] (Comparative Manufacturing Example 1) Polyester polyol resin (CPE1) In a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 36.40 parts of ethylene glycol, 84.35 parts of adipic acid, and 0.005 parts of titanium tetraisopropoxide were charged, and the internal temperature was maintained at 220° C. by gradually heating so that the temperature at the top of the rectification tube did not exceed 100° C. When the acid value became 0.5 mg KOH / g or less, the esterification reaction was terminated, and then 66.67 parts of ethyl acetate were charged to obtain a polyester liquid CPE1 having a number average molecular weight of 9000.
[0145] (Comparative Manufacturing Example 2) Polyester urethane resin (CPEU21) Into a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 43.90 parts of ethylene glycol, 74.41 parts of adipic acid, and 0.005 parts of titanium tetraisopropoxide were charged, and the inside temperature was maintained at 220° C. by gradually heating so that the temperature at the top of the rectification tube did not exceed 100° C. When the acid value became 0.5 mg KOH / g or less, the esterification reaction was terminated, and a polyester intermediate CPE2 having a number average molecular weight of 500 was obtained.
[0146] Next, 72.44 parts of polyester polyol (CPE2), 27.56 parts of isophorone diisocyanate, and 25.00 parts of ethyl acetate were charged into a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, and reacted at 70°C for 15 hours under a nitrogen stream, and then 41.67 parts of ethyl acetate were added to obtain a polyester urethane resin (CPEU21). The obtained polyurethane resin solution (CPEU21) had a resin solid concentration of 60% by weight.
[0147] (Comparative Manufacturing Example 3) Polyester urethane resin (CPEU31) In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube, 57.97 parts of neopentyl glycol adipate diol (hydroxyl value: 56.0 mg KOH / g), 14.49 parts of polyethylene glycol (hydroxyl value: 280.0 mg KOH / g) having a number average molecular weight of 400, and 21.49 parts of isophorone diisocyanate were charged and reacted for 15 hours at 90 ° C. under a nitrogen gas flow to produce a urethane prepolymer having an isocyanate group, and then 50.0 parts of ethyl acetate were added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 0.10 parts of dibutylamine, 5.94 parts of isophorone diamine, 101.67 parts of ethyl acetate and 81.67 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C. for 5 hours to obtain a polyurethane resin (CPEU31) solution. The obtained polyurethane resin solution (CPEU31) had a resin solids concentration of 30% by weight.
[0148] (Liquid Printing Ink Examples and Comparative Examples) (Method of manufacturing liquid printing ink) The mixtures mixed in the ratios shown in the table were kneaded using a Dyno-Mill (manufactured by Willy & Bachofen Co., Ltd.) to prepare the inks described in the Examples and Comparative Examples.
[0149] (How to create printed materials) The liquid printing ink obtained by the above manufacturing method was diluted with the same ratio of mixed organic solvent used for ink preparation, and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd. Using a gravure printing machine (manufactured by DIC Engineering Co., Ltd.) equipped with a gravure plate having a plate depth of 35 μm, a solid print was made on the corona-treated surface of a biaxially oriented polypropylene film (OPP, P2161 manufactured by Toyobo Co., Ltd., thickness 20 μm) that had been corona-discharge-treated on one side. The prints using the hardener were aged at 40°C for one day.
[0150] <Evaluation method for liquid printing ink prints> (Blocking resistance) The films were overlapped so that the printed and non-printed surfaces of the prints obtained using the above-mentioned print production method were in contact, a load of 10 kgf / cm2 was applied, and the prints were left in an environment of 40°C for 12 hours.After being removed, the state of ink transfer to the non-printed surface was visually evaluated using the following five-point scale. (Evaluation Criteria) 5: 0% of the ink is transferred to the non-printed surface, and no transfer is observed. 4: Less than 5% metastasis is seen. 3: Metastasis is seen in 5% to less than 10% of cases. 2: Metastasis is observed in 10% to less than 20% of cases. 1: More than 20% of the metastatic volume has metastasized. Recyclability: Taking into consideration the damage to recycling facilities, materials that do not contain chlorinated vinyl monomers or polymers are rated as "Good", and materials that do contain chlorinated vinyl monomers or polymers are rated as "Poor".
[0151] (Adhesion) Evaluation was performed by pressing cellophane tape manufactured by Nichiban onto the printed surface obtained by the above-mentioned print production method and peeling it off, and measuring the peeled area. (Evaluation Criteria) 5: No peeling 4: Peeling of 10% or less is observed. 3: Peeling of 10 or more and 30% or less is observed. 2: Peeling is observed at 30% to 60%. 1: More than 60% is peeled off.
[0152] (Appearance after lamination) DIC solvent-free adhesive 2K-SF-900A / HA-930B was applied at a coating weight of 2g / m using a non-solvent laminator. 2 The laminate was coated so that the result was as shown below, and then laminated with a composition of OPP film (Toyobo P2161) / ink / solvent-free adhesive / aluminum-deposited CPP film (Toray Film Processing 2203), and the appearance after lamination was evaluated. ◯: No glittering or other defects in the grain appearance, and high hiding power. ×: Poor grain appearance (sparkle) and poor hiding power.
[0153] [Table 1]
[0154] [Table 2]
[0155] [Table 3] *Paslim MB 100A / MB-520B
[0156] [Table 4]
[0157] [Table 5]
[0158] The raw materials in the table are as follows: R-780: Titanium oxide pigment manufactured by Ishihara Sangyo Kaisha, Ltd. Average particle size 0.24μm, oil absorption 33 Pigment dispersion (Solsperse 24000 manufactured by Lubrizol dissolved in n-propyl acetate to a concentration of 10%) Filler: HM6025: Mica (KAL2(ALSi3O 10 )(OH)2), non-swelling, plate-like, average particle size 10μm, aspect ratio 100 or more Ketone-aldehyde resin: Variplus SK solution: (TEGO® Varipuls SK, number average molecular weight 800, hydroxyl value 325 mgKOH / g, manufactured by EVONIK) was dissolved in ethyl acetate to give a 50% solids solution. The softening point is 110-120°C. CAP: Cellulose acetate propionate (CAP-482-0.5, Eastman) was dissolved in ethyl acetate to prepare a 20% solids solution. The softening point is 188-210°C. PVB: Polyvinyl butyral resin-containing solution (Mobital B16H, manufactured by Kuraray) was dissolved in ethyl acetate to give a 15% solids solution. The Tg was 63°C. Vinyl chloride-vinyl acetate copolymer: Solvine A (manufactured by Nissin Chemical Industry Co., Ltd.) is a vinyl chloride-vinyl acetate copolymer resin with a resin composition of "vinyl chloride / vinyl acetate / vinyl alcohol = 92 / 3 / 5 (weight ratio)" (number average molecular weight 30,000, glass transition point 76°C, K value = 48) was dissolved in ethyl acetate to make a 15% solids solution. Chlorinated polypropylene resin: Super Chlon 360T (manufactured by Nippon Paper Industries Co., Ltd.) (chlorination degree 31%, solid content 60%) Hardener: Takenate D110N (Mitsui Chemicals' XDI polyisocyanate (with aromatic ring), non-volatile content: 75%) Adhesive: DIC Corporation's general-purpose adhesive "DIC Dry LX-470 / SP-60" and gas barrier adhesive "PASLIM MB100A / MB-520B" were used.
[0159] (Method of manufacturing laminate) The liquid printing ink obtained by the above-mentioned manufacturing method was used to print on a 30 μm thick OPP film (P2161 manufactured by Toyobo) using a gravure printing machine equipped with a laser gravure plate having a plate depth of 25 μm, and then the print was dried with a dryer to obtain a printed matter. Next, the adhesive was applied using a bar coater in a coating amount of 2.0 g / m 2 The adhesive layer was formed by applying the adhesive to the printed layer so that the thickness of the adhesive was 3.5 gsm (solid content, LX-470 / SP-60) or 3.5 gsm (solid content, PASLIM MB100A / MB-520B), and the dilution solvent was evaporated using a dryer set at 70°C to dry the film, forming an adhesive layer. The OPP film and the 25 μm thick CPP film (Toyobo Pylen Film CT P1128 30 μm) were bonded together via the adhesive layer, and then aged at 40°C for 3 days to obtain a laminate.
[0160] <Laminate evaluation method> (Oxygen barrier properties) After aging, the laminate was measured for oxygen barrier properties in an atmosphere at 23°C. The unit is cc / m2·day·atm. Note that RH stands for humidity. Oxygen barrier properties (OTR) measurement at 23°C / 0% RH: MOCON OX-TRAN 2 / 21 constant pressure method (compliant with JIS K 7126) (Lamination strength (T-type peeling)) The laminate after aging was cut perpendicular to the coating direction to a width of 15 mm, and the base film and the sealant film were peeled using a Tensilon universal testing machine manufactured by Orientec Co., Ltd. at an atmospheric temperature of 25°C and a peel speed of 300 mm / min. The tensile strength when peeled using a T-type peel method was recorded as the adhesive strength.
[0161] The results are shown in the table above. From the above results, it is clear that the laminate using the ink of the present invention has excellent oxygen barrier properties.
Claims
1. an amorphous polyester resin (A) and / or an amorphous polyester urethane resin (B) having an ester skeleton which is a polycondensate of a polycarboxylic acid component containing at least one of an ortho-oriented aromatic dicarboxylic acid or an anhydride thereof and a polyhydric alcohol component containing at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol; Resin (C) having a glass transition temperature (Tg) or softening point of 40° C. or higher A liquid printing ink comprising:
2. 2. The liquid printing ink according to claim 1, wherein the resin (C) is cellulose acetate propionate (C1) and / or cellulose acetate butyrate (C2).
3. 3. The liquid printing ink according to claim 1 or 2, characterized in that the resin (C) contains at least one selected from the group consisting of a ketone-aldehyde resin (C3), a hydrogenated ketone-aldehyde resin (C4), and a urethane compound (C5) consisting of the hydrogenated ketone-aldehyde resin (C4) and an organic diisocyanate.
4. 3. The liquid printing ink according to claim 1 or 2, which contains a chlorinated polyolefin resin (G).
5. 3. The liquid printing ink according to claim 1, which contains a polyisocyanate (H).
6. 3. The liquid printing ink according to claim 1, which contains a filler (I) having an aspect ratio of 50 or more.
7. 3. The liquid printing ink according to claim 1, wherein the amorphous polyester resin (A) and the amorphous urethane resin (B) have a number average molecular weight of 3,000 to 50,000 and are linear or branched.
8. 3. The liquid printing ink according to claim 1, further comprising a colorant (D).
9. 9. A liquid printing ink according to claim 8, wherein said colorant (D) is titanium oxide.
10. 3. The liquid printing ink according to claim 1, further comprising an organic solvent (E).
11. 10. The liquid printing ink according to claim 9, wherein the organic solvent (E) is free of aromatic solvents and ketone solvents.
12. A printed matter printed with the liquid printing ink according to claim 1 or 2.
13. A laminate or a packaging bag comprising the printed matter according to claim 12.
14. 3. A laminate or packaging bag comprising, in this order, at least a first substrate, a printed layer printed on the first substrate, a gas barrier adhesive layer or a gas barrier coating layer, and a second substrate, wherein the printed layer is a liquid printing ink according to claim 1 or 2.
15. The laminate or packaging bag according to claim 14, wherein the first substrate is an olefin-based substrate.
Citation Information
Patent Citations
Roof slab device of tank type fast breeder
JP1984075189A
Production of optically active (r) or (s)-4-hydroxy-1-pentene
JP1988072635A
Adhesive and oxygen barrier film using the same
JP2012057033A
Ink composition and packaging material
JP2018024798A
Liquid printing ink, printed matter, and laminate
JP2022112187A